Wpływ inwentaryzacji kształtu przekrojów kanałów na dokładność przepływomierza profilujacego = Effect of the inventory of cross channel shape on accuracy of rofiling flowmeter - Nowogoński, Ireneusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents an analysis of measurement errors during reconstruction of cross-sectional shape of the channel for the accuracy of profiling flowmeters. The influence of measurement errors and measurement planning on the obtained results has been shown.
Keywords: monitoring; kanalizacja ogólnospławna; combined sewer systems